Sociodemographic and Psychosocial Determinants of Cardiovascular Health among Women Patients in Thika and Kiambu Level Five Hospitals in Kiambu County, Kenya - Chepchumba, Sharon Lesa; Akinyi, Mary; Mapesa, Job (International Journal of Professional Practice, 2026)
Cardiovascular disease (CVD) remains a predominant global health issue, with women experiencing higher mortality rates and poorer outcomes compared to men. This disparity, influenced by sociodemographic, psychosocial, and clinical factors, is underexplored in low- and middle-income countries (LMICs). In Sub-Saharan Africa, the rising prevalence of CVD driven by urbanisation and lifestyle changes underscores the need for targeted research in regions such as Kiambu County, Kenya. This study assessed the sociodemographic, psychosocial, clinical, dietary, and health literacy factors associated with women's cardiovascular health at Thika and Kiambu Level 5 hospitals. The target population consisted of 400 female patients exhibiting CVD symptoms. A sample size of approximately 285 was determined using the Mugenda and Mugenda (2013) formula, based on Kenya's hypertension prevalence of 24.5%. Data was collected through structured questionnaires using simple random sampling. Statistical analysis, including chi-square tests and regression modelling, was conducted to identify key predictors of CVD. Analysis revealed that individuals aged 19-43 years accounted for 19.5% of diagnoses. Among participants, 31.3% had hypertension and 33.5% had diabetes. Psychosocial results showed 13.8% were diagnosed with depression, while 31.5% reported high stress levels. Dietary habits included consumption of refined foods (24%) and fried foods (21%). Furthermore, 27.5% lacked CVD knowledge and 29.8% had not received nutritional education. These findings emphasise the need for targeted health literacy interventions and comprehensive public health strategies by the Kiambu County Department of Health Services to address hypertension, diabetes, and psychosocial stress. Such measures are crucial for mitigating CVD risks among women in Kiambu County and similar LMIC regions.